TINGKAT KECEMASAN REMAJA MENGENAI PEMBERITAAN COVID-19 DI MEDIA SOSIAL - Ade Viratama; Femi Oktaviani (Metakom, 2021)
The amount of news about Covid 19, without any filtering of information can cause various reactions that appear simultaneously, for example, such as feelings of anxiety, especially those that occur to teenagers, because teenagers can be said to be an age that is still unstable in dealing with unexpected conditions. Therefore, this study aims to determine the perception and level of anxiety that occurs to teenagers regarding news about Covid-19. The method in this research is using qualitative research methods with phenomenological studies. The subjects of this study were students of SMK PGRI Bungbulang Kab. Garut who had experienced anxiety disorders due to the news during the covid-19 pandemic. The results of this study indicate that the formation of anxiety symptoms actually starts from a small fear that continues to gradually become larger because it is influenced by the high intensity of social media use, and information that is not filtered so that they experience symptoms that lead to excessive anxiety that occurs. and experienced in the mass pandemic of students at SMK PGRI Bungbulang Kab. arrowroot.